High-performance thermoplastic starch-based TPS / PBAT blended plastic and preparation method thereof

By introducing dynamic imine bonds into TPS and PBAT to form a reversible cross-linked network, the problem of poor compatibility between TPS and PBAT was solved, enabling the preparation of high-performance thermoplastic starch-based blended plastics and improving the mechanical properties and recyclability of the materials.

CN119286004APending Publication Date: 2025-01-10HUBEI UNIV OF TECH

Patent Information

Application Number
CN202411493573.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing thermoplastic starch (TPS) has poor compatibility with biodegradable PBAT resin, which leads to a decline in its performance during processing and recycling, making it difficult to compete with petroleum-based plastics.

Method used

High-performance thermoplastic starch-based blends were prepared using a three-step method. Dynamic imine bonds were introduced into TPS and PBAT, and methyl 3-aminocrotonate (AAME) was used as a graft monomer to carry out melt graft copolymerization with TPS/PBAT. Subsequently, a reversible crosslinking network was formed with terephthalaldehyde (TPA) to achieve dynamic covalent bonding.

Benefits of technology

It significantly improves the compatibility and mechanical properties of TPS and PBAT, enhances the high-temperature melt processing performance of the material, reduces molecular chain damage, realizes reversible dynamic cross-linking and recycling of the material, reduces costs and expands the application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286004A_ABST
    Figure CN119286004A_ABST
Patent Text Reader

Abstract

The invention provides a high-performance thermoplastic starch-based TPS / PBAT blended plastic and a preparation method thereof. The preparation method comprises the following steps: preparing pre-plasticized starch, carrying out melt blending on the obtained pre-plasticized starch TPS, poly (butylene adipate-co-butylene adipate) PBAT, a grafting agent and an initiator, cooling, and drying to obtain a grafting material; and putting the grafted material and a cross-linking agent into an internal mixer for melt blending, cooling and drying to obtain the high-performance thermoplastic starch-based blended plastic TPS / PBAT. The method is suitable for industrial large-scale mass production and recycling treatment, the recycling treatment can be realized by directly adopting plastic processing methods such as an internal mixer and an extruder, and the high-performance thermoplastic starch-based blended plastic can be obtained again under the condition that the molecular chain part is degraded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of environmentally friendly regeneration, and specifically relates to a high-performance thermoplastic starch-based TPS / PBAT blended plastic modified by dynamic cross-linking of imine bonds and a preparation method thereof. Background Art

[0002] As one of the most abundant natural polymers in nature, thermoplastic starch (TPS) has the advantages of low cost and biodegradability. However, this type of bio-based plastic is difficult to compete with petroleum-based plastics due to its poor toughness, high modulus, poor thermal stability, poor processing fluidity, and potential impacts such as raw materials competing with people for food. There are no chemical bonds between the long chains of macromolecules in thermoplastic materials, and the shape of the entire material is maintained more by the entanglement between the chains. Therefore, it is easy to melt, deform and process in a molten state. At the same time, the molecular chains will break and decompose during the use cycle and cyclic processing, and the mechanical properties and performance will decrease significantly. In addition to the entanglement between molecular chains, thermosetting plastics also have irreversible bonds connecting the chains to each other. This cross-linked network gives it excellent mechanical properties and dimensional stability during use. However, thermosetting plastics cannot be melted in a molten state, and cannot be processed and molded for secondary processing, and are almost impossible to recycle. The dynamic covalent chemistry proposed by Rowan et al. [Rowan SJ, Cantrill SJ, Cousins ​​GRL, et al. Dynamic covalent chemistry [J]. Angewandte Chemie International Edition, 2002, 41 (6): 898-952.] provides a possibility for extending the life cycle of traditional thermoplastics. Dynamic covalent chemistry involves a series of reversibly balanced covalent chemical reactions, the core of which is the dynamic balance of the continuous breaking and reconstruction of reversible covalent bonds. The melt-grafted modified starch proposed by Wang Peizhang et al. [Wang Peizhang, Liu Xue. Preparation and performance study of reaction extrusion melt-grafted modified starch / PE-LD foaming material [J]. China Plastics, 2008, 22 (10): 4. DOI: CNKI: SUN: ZGSU. 0. 2008-10-013.] provides a possibility for introducing functional groups into starch after melt grafting through an extruder or internal mixer. Solution grafting requires a large amount of solvent, which is highly polluting, costly and difficult to apply and promote in industrial production. Melt grafting overcomes these shortcomings of solution grafting. CN202410022525.9 discloses a method for preparing a graphene / polyurea self-healing and recyclable thermally conductive composite material with synergistic effects of hydrogen bonds and dynamic imine bonds. In the polyurea synthesis process, the dynamic imine bonds are introduced by Schiff base reaction to prepare it. By introducing dynamic imine bonds in polyurea, the material is endowed with good self-healing ability. The cross-linked network it forms has dynamic characteristics. Under high temperature conditions, the dynamic imine bonds break and reorganize, giving the cross-linked material the performance of thermoplastic processing and recycling again, increasing the service life of the material and reducing resource waste and environmental problems.However, the matrix material of this invention introduces functional groups during the macromolecular synthesis process. The preparation process requires special synthesis reaction equipment and the process is complicated, which makes it difficult to promote and apply industrially and is not universal for natural macromolecules.

[0003] PBAT (polybutylene terephthalate-adipate) is a fully biodegradable polyester with good toughness, good molding and processing performance, and high water resistance, but TPS is not compatible with PBAT resin. Therefore, in the process of recycling plastics, it is urgent to develop a method with low cost, excellent recycling performance, simple process and universal applicability. Summary of the invention

[0004] The present invention is made to solve the above problems, and aims to provide a method for preparing high-performance thermoplastic starch-based blended plastics, which has simple process, easy operation, readily available raw materials, low cost, and is suitable for industrial large-scale mass production.

[0005] In order to achieve the above object, the present invention adopts the following scheme:

[0006] A method for preparing a high-performance thermoplastic starch-based blended plastic TPS / PBAT comprises the following steps:

[0007] Step (1), mixing starch and starch plasticizer and letting the mixture stand to obtain pre-plasticized starch;

[0008] Step (2), melt-blending the obtained pre-plasticized starch with PBAT, AAME and an initiator, cooling and drying to obtain a grafted material;

[0009] Step (3), melt blending the obtained grafted material with TPA, cooling, and drying to obtain a high-performance thermoplastic starch-based blended plastic TPS / PBAT.

[0010] Furthermore, in step (1), the mass ratio of starch, starch plasticizer and water is (70-80):(20-40).

[0011] Furthermore, the starch plasticizer is selected from any one or more of water, glycerol, propylene glycol, and sorbitol.

[0012] Furthermore, the starch plasticizer comprises water and any one or more of glycerol, propylene glycol and sorbitol.

[0013] Furthermore, in step (1), the mixture of starch and starch plasticizer is placed in a sealed environment at room temperature for 10 to 20 hours; for example, the mixture of starch and starch plasticizer is placed in a sealed bag in an environment of 25° C. for 12 hours.

[0014] Furthermore, in step (1), starch and starch plasticizer are blended using a high-speed mixer for a stirring time of 8 to 20 minutes.

[0015] Furthermore, in step (2), the mass ratio of pre-plasticized starch to PBAT is (80-90):(10-20).

[0016] Furthermore, the mass ratio of preplasticized starch to PBAT is 85:15.

[0017] Furthermore, in step (2), the mass of AAME is 4%-6% of the total mass of pre-plasticized starch and PBAT.

[0018] Furthermore, in step (2), the mass of the initiator is 0.1%-0.25% of the total mass of the pre-plasticized starch and PBAT.

[0019] Furthermore, in step (3), the amount of TPA added is 0.35%-0.5% of the total mass of the pre-plasticized starch and PBAT.

[0020] Furthermore, the initiator is dicumyl peroxide (DCP).

[0021] Furthermore, the temperature of melt blending in step (2) and step (3) is 145-160°C.

[0022] Furthermore, step (2) and step (3) are melt blended using an internal mixer, and the speed of the internal mixer is 25-35 r / min.

[0023] The present invention also provides a high-performance thermoplastic starch-based TPS / PBAT blended plastic, which is prepared by the above method.

[0024] The present invention effectively connects the two molecular chains together in a dynamic cross-linked network melt grafting based on Schiff base, significantly improving the compatibility of TPS and PBAT resin. At the same time, due to the change of temperature, the state of the reversible bond will be disconnected or reorganized with the temperature. Figure 1As shown, in the first step, 3-aminocrotonic acid methyl ester (3-Aminocrotonic Acid MethylEster, AAME) is used as a grafting monomer to carry out a melt grafting copolymerization reaction with TPS / PBAT. AAME contains highly reactive carbon-carbon double bonds. Under the action of high shear, thermal initiation, and initiator, the double bonds are opened to react with TPS / PBAT molecular chains to produce free radicals. The highly reactive carbon-carbon double bonds in AAME also have the function of further chain extension, which can terminate the chain through free radical chain extension reaction to form a long-branched multi-primary amine functional group structure on the TPS / PBAT molecular chain, so that TPS / PBAT does not need a solution method to graft macromolecules, and obtains high primary amine reactivity in a melt grafting reaction that is conducive to industrial production; in the second step, the functionalized grafting material is used to react with the cross-linking agent terephthalaldehyde (TPA) for a melt reaction, and a reversible exchange reaction occurs between the amino and aldehyde groups at high temperature to form a dynamic covalent network, and finally a high-performance, recyclable branched dynamic cross-linked thermoplastic starch-based blended plastic is obtained.

[0025] Compared with the prior art, the present invention has the following advantages and significant progress:

[0026] (1) The present invention selects starch with low cost and a small amount of biodegradable plastic PBAT, and introduces a reversible dynamic crosslinking network through a two-step method by first branching and grafting, and then dynamic crosslinking. The high-temperature melt processing performance of the reversible dynamic crosslinking is better, which reduces the damage of the molecular chain during high-temperature processing, improves its high performance, improves the tensile strength and elastic modulus, and expands its application range. At the same time, it avoids the molecular chain breakage caused by one-step crosslinking, or the problems of reduced elongation at break and reduced processing performance caused by excessive crosslinking.

[0027] (2) The present invention can achieve the introduction of a reversible dynamic cross-linking network through simple melting conditions, and has a short reaction time, a simple process, and can achieve continuous production. During recycling, it can also be directly processed by processing methods such as internal mixers and extruders. Even if some molecular chains are degraded during the recycling process, their mechanical properties can remain basically stable after multiple cycles of recycling, thereby increasing the value of the recycled material. The main matrix raw material is starch, which has a lower cost than other degradable materials and is a renewable substance that can be continuously generated in nature. It has excellent degradation ability and reduces pollution to the environment. It is of great significance to reduce the preparation and recycling costs of reversible dynamic cross-linking polymers and expand their scope of application. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a schematic diagram of the microstructure of the branched dynamically cross-linked thermoplastic starch-based blended plastic prepared in the present invention. DETAILED DESCRIPTION

[0029] The specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. For ease of comparison, in the following examples and comparative examples.

[0030] In the following embodiments:

[0031] The recorded parts are all parts by weight;

[0032] The initiator used was DCP;

[0033] The grafting agent is AAME.

[0034] Example 1

[0035] Step 1: Weigh 70 parts of starch, 30 parts of glycerol, and 10 parts of water and put them into a high-speed blender and stir for 10 minutes. After the starch and glycerol are blended, put them into a sealed bag and place them in an environment of 25°C for 12 hours to obtain pre-plasticized starch.

[0036] Step 2: 85 parts of pre-plasticized starch, 15 parts of PBAT, 0.1 parts of initiator, and 6 parts of grafting agent are mixed evenly.

[0037] Step 3: Place the mixture in step 2 into an internal mixer for melt blending. The temperature of the internal mixer is 150° C. and the speed is 30 r / min. After cooling and drying, the grafted material is obtained.

[0038] Step 4: The grafted material obtained in step 3 was mixed evenly with 0.35 parts of cross-linking agent TPA.

[0039] Step 5: Put the mixture in step 4 into an internal mixer for melt blending. The temperature of the internal mixer is 150°C and the speed is 30r / min. After cooling and drying, high-performance recyclable branched dynamic cross-linked TPS / PBAT resin is obtained. Sample preparation and testing are performed to obtain the original mechanical properties.

[0040] Step 6: The sample prepared in step 5 was mixed in an internal mixer at a speed of 30 r / min and a temperature of 150° C. for 30 min, and then the sample was tested to obtain the recycled mechanical properties. The sample was treated in the above manner for three cycles.

[0041] Example 2

[0042] Step 1: Weigh 70 parts of starch, 30 parts of glycerol, and 10 parts of water and put them into a high-speed blender and stir for 10 minutes. After the starch and glycerol are blended, put them into a sealed bag and place them in an environment of 25°C for 12 hours to obtain pre-plasticized starch.

[0043] Step 2: Mix 85 parts of pre-plasticized starch, 15 parts of PBAT, 0.1 parts of initiator and 5 parts of grafting agent evenly.

[0044] Step 3: Place the mixture in step 2 into an internal mixer for melt blending. The temperature of the internal mixer is 150° C. and the speed is 30 r / min. After cooling and drying, the grafted material is obtained.

[0045] Step 4: The grafted material obtained in step 3 is mixed evenly with 0.3 parts of cross-linking agent TPA.

[0046] Step 5: Put the mixture in step 4 into an internal mixer for melt blending. The temperature of the internal mixer is 150°C and the speed is 30r / min. After cooling and drying, high-performance recyclable branched dynamic cross-linked TPS / PBAT resin is obtained. Sample preparation and testing are performed to obtain the original mechanical properties.

[0047] Step 6: The sample prepared in step 5 was mixed in an internal mixer at a speed of 30 r / min and a temperature of 150° C. for 30 min, and then the sample was tested to obtain the recycled mechanical properties. The sample was treated in the above manner for three cycles.

[0048] Example 3

[0049] Step 1: Weigh 70 parts of starch, 30 parts of glycerol, and 10 parts of water and put them into a high-speed blender and stir for 10 minutes. After the starch and glycerol are blended, put them into a sealed bag and place them in an environment of 25°C for 12 hours to obtain pre-plasticized starch.

[0050] Step 2: 85 parts of pre-plasticized starch, 15 parts of PBAT, 0.15 parts of initiator, and 5.5 parts of grafting agent are mixed evenly.

[0051] Step 3: Place the mixture in step 2 into an internal mixer for melt blending. The temperature of the internal mixer is 150° C. and the speed is 30 r / min. After cooling and drying, the grafted material is obtained.

[0052] Step 4: The grafted material obtained in step 3 is mixed evenly with 0.4 parts of cross-linking agent TPA.

[0053] Step 5: Put the mixture in step 4 into an internal mixer for melt blending. The temperature of the internal mixer is 150°C and the speed is 30r / min. After cooling and drying, high-performance recyclable branched dynamic cross-linked TPS / PBAT resin is obtained. Sample preparation and testing are performed to obtain the original mechanical properties.

[0054] Step 6: The sample prepared in step 5 was mixed in an internal mixer at a speed of 30 r / min and a temperature of 150° C. for 30 min, and then the sample was tested to obtain the recycled mechanical properties. The sample was treated in the above manner for three cycles.

[0055] Example 4

[0056] Step 1: Weigh 70 parts of starch, 30 parts of glycerol, and 10 parts of water and put them into a high-speed blender and stir for 10 minutes. After the starch and glycerol are blended, put them into a sealed bag and place them in an environment of 25°C for 12 hours to obtain pre-plasticized starch.

[0057] Step 2: Mix 85 parts of pre-plasticized starch, 15 parts of PBAT, 0.2 parts of initiator and 4.5 parts of grafting agent evenly.

[0058] Step 3: Place the mixture in step 2 into an internal mixer for melt blending. The temperature of the internal mixer is 150° C. and the speed is 30 r / min. After cooling and drying, the grafted material is obtained.

[0059] Step 4: The grafted material obtained in step 3 was mixed evenly with 0.45 parts of cross-linking agent TPA.

[0060] Step 5: Put the mixture in step 4 into an internal mixer for melt blending. The temperature of the internal mixer is 150°C and the speed is 30r / min. After cooling and drying, high-performance recyclable branched dynamic cross-linked TPS / PBAT resin is obtained. Sample preparation and testing are performed to obtain the original mechanical properties.

[0061] Step 6: The sample prepared in step 5 was mixed in an internal mixer at a speed of 30 r / min and a temperature of 150° C. for 30 min, and then the sample was tested to obtain the recycled mechanical properties. The sample was treated in the above manner for three cycles.

[0062] Example 5

[0063] Step 1: Weigh 70 parts of starch, 30 parts of glycerol, and 10 parts of water and put them into a high-speed blender and stir for 10 minutes. After the starch and glycerol are blended, put them into a sealed bag and place them in an environment of 25°C for 12 hours to obtain pre-plasticized starch.

[0064] Step 2: Mix 85 parts of pre-plasticized starch, 15 parts of PBAT, 0.25 parts of initiator and 4 parts of grafting agent evenly.

[0065] Step 3: Place the mixture in step 2 into an internal mixer for melt blending. The temperature of the internal mixer is 150° C. and the speed is 30 r / min. After cooling and drying, the grafted material is obtained.

[0066] Step 4: The grafted material obtained in step 3 is mixed evenly with 0.5 parts of cross-linking agent TPA.

[0067] Step 5: Put the mixture in step 4 into an internal mixer for melt blending. The temperature of the internal mixer is 150°C and the speed is 30r / min. After cooling and drying, high-performance recyclable branched dynamic cross-linked TPS / PBAT resin is obtained. Sample preparation and testing are performed to obtain the original mechanical properties.

[0068] Step 6: The sample prepared in step 5 was mixed in an internal mixer at a speed of 30 r / min and a temperature of 150° C. for 30 min, and then the sample was tested to obtain the recycled mechanical properties. The sample was treated in the above manner for three cycles.

[0069] Comparative Example 1

[0070] Step 1: Weigh 70 parts of starch, 30 parts of glycerol, and 10 parts of water and put them into a high-speed blender and stir for 10 minutes. After the starch and glycerol are blended, put them into a sealed bag and place them in an environment of 25°C for 12 hours to obtain pre-plasticized starch.

[0071] Step 2: 85 parts of pre-plasticized starch and 15 parts of PBAT, mix well.

[0072] Step 3: Place the mixture in step 2 into an internal mixer for melt blending at a temperature of 150° C. and a rotation speed of 30 r / min, followed by cooling and drying.

[0073] Step 4: Place the materials in step 3 into an internal mixer for melt blending. The temperature of the internal mixer is 150° C. and the speed is 30 r / min. After cooling and drying, the samples are prepared for testing to obtain the original mechanical properties.

[0074] Step 5: The sample prepared in step 5 was mixed in an internal mixer at a speed of 30 r / min and a temperature of 150° C. for 30 min, and then the sample was tested to obtain the recycled mechanical properties. The sample was treated in the above manner for three cycles.

[0075] Comparative Example 2

[0076] Step 1: Weigh 70 parts of starch, 30 parts of glycerol, and 10 parts of water and put them into a high-speed blender and stir for 10 minutes. After the starch and glycerol are blended, put them into a sealed bag and place them in an environment of 25°C for 12 hours to obtain pre-plasticized starch.

[0077] Step 2: Mix 85 parts of pre-plasticized starch, 15 parts of PBAT, and 0.2 parts of initiator evenly.

[0078] Step 3: Place the mixture in step 2 into an internal mixer for melt blending at a temperature of 150° C. and a rotation speed of 30 r / min, followed by cooling and drying.

[0079] Step 4: Place the materials in step 3 into an internal mixer for melt blending. The temperature of the internal mixer is 150° C. and the speed is 30 r / min. After cooling and drying, the samples are prepared for testing to obtain the original mechanical properties.

[0080] Step 5: The sample prepared in step 4 was mixed in an internal mixer at a speed of 30 r / min and a temperature of 150° C. for 30 min, and then the sample was tested to obtain the recycled mechanical properties. The sample was treated in the above manner for three cycles.

[0081] Comparative Example 3

[0082] Step 1: Weigh 70 parts of starch, 30 parts of glycerol, and 10 parts of water and put them into a high-speed blender and stir for 10 minutes. After the starch and glycerol are blended, put them into a sealed bag and place them in an environment of 25°C for 12 hours to obtain pre-plasticized starch.

[0083] Step 2: Mix 85 parts of pre-plasticized starch, 15 parts of PBAT, 0.2 parts of initiator and 5 parts of grafting agent evenly.

[0084] Step 3: Place the mixture in step 2 into an internal mixer for melt blending. The temperature of the internal mixer is 150° C. and the speed is 30 r / min. After cooling and drying, the grafted material is obtained.

[0085] Step 4: Place the mixture in step 3 into an internal mixer for melt blending. The temperature of the internal mixer is 150° C. and the speed is 30 r / min. After cooling and drying, the sample is prepared for testing to obtain the original mechanical properties.

[0086] Step 5: The sample prepared in step 4 was mixed in an internal mixer at a speed of 30 r / min and a temperature of 150° C. for 30 min, and then the sample was tested to obtain the recycled mechanical properties. The sample was treated in the above manner for three cycles.

[0087] Comparative Example 4

[0088] Step 1: Weigh 70 parts of starch, 30 parts of glycerol, and 10 parts of water and put them into a high-speed blender and stir for 10 minutes. After the starch and glycerol are blended, put them into a sealed bag and place them in an environment of 25°C for 12 hours to obtain pre-plasticized starch.

[0089] Step 2: Mix 85 parts of pre-plasticized starch, 15 parts of PBAT, and 0.2 parts of initiator evenly.

[0090] Step 3: Place the mixture in step 2 into an internal mixer for melt blending at a temperature of 150° C. and a rotation speed of 30 r / min, followed by cooling and drying.

[0091] Step 4: Mix the material obtained in step 3 with 0.3 parts of cross-linking agent TPA.

[0092] Step 5: Place the mixture in step 4 into an internal mixer for melt blending. The temperature of the internal mixer is 150° C. and the speed is 30 r / min. After cooling and drying, the sample is prepared for testing to obtain the original mechanical properties.

[0093] Step 6: The sample prepared in step 5 was mixed in an internal mixer at a speed of 30 r / min and a temperature of 150° C. for 30 min, and then the sample was tested to obtain the recycled mechanical properties. The sample was treated in the above manner for three cycles.

[0094] Comparative Example 5

[0095] Step 1: Weigh 70 parts of starch, 30 parts of glycerol, and 10 parts of water and put them into a high-speed blender and stir for 10 minutes. After the starch and glycerol are blended, put them into a sealed bag and place them in an environment of 25°C for 12 hours to obtain pre-plasticized starch.

[0096] Step 2: Mix 70 parts of pre-plasticized starch, 30 parts of PBAT, 0.1 parts of initiator and 5 parts of grafting agent evenly.

[0097] Step 3: Place the mixture in step 2 into an internal mixer for melt blending. The temperature of the internal mixer is 150° C. and the speed is 30 r / min. After cooling and drying, the grafted material is obtained.

[0098] Step 4: The grafted material obtained in step 3 is mixed evenly with 0.3 parts of cross-linking agent TPA.

[0099] Step 5: Put the mixture in step 4 into an internal mixer for melt blending. The temperature of the internal mixer is 150°C and the speed is 30r / min. After cooling and drying, high-performance recyclable branched dynamic cross-linked TPS / PBAT resin is obtained. Sample preparation and testing are performed to obtain the original mechanical properties.

[0100] Step 6: The sample prepared in step 5 was mixed in an internal mixer at a speed of 30 r / min and a temperature of 150° C. for 30 min, and then the sample was tested to obtain the recycled mechanical properties. The sample was treated in the above manner for three cycles.

[0101] The mechanical properties of the original samples of the high-performance recycled branched dynamic cross-linked TPS / PBAT resin obtained in the above examples and comparative examples and the mechanical properties of the recycled samples are shown in Table 1:

[0102] Table 1: Mechanical properties of the original TPS / PBAT resin sample and the mechanical properties of the recycled sample

[0103]

[0104]

[0105]

[0106] Comparative Example 1 is unmodified TPS / PBAT. From Table 1, it can be seen that its mechanical properties are greatly reduced after multiple mixing cycles. After three cycles, the tensile strength is reduced by 50.75% compared with the original performance, and the elongation at break is reduced by 70.75%, which loses its effective performance. In Comparative Example 2, a small amount of permanent chemical cross-linking bonds were introduced by adding DCP, and in Comparative Example 3, amino groups were introduced on the side groups, but a cross-linking agent was lacking. In Comparative Example 4, a cross-linking agent was added to TPS / PBAT, but amino groups were not introduced on the side groups. After three banburying cycles, the tensile strength of Comparative Examples 2 and 4 was greatly reduced by 54.75% to 67.74% compared with the original performance. At the same time, the elastic modulus was low, and the elongation at break dropped sharply to 74.56% to 77.98% compared with the original performance. In Comparative Example 5, the ratio of TPS and PBAT (70 / 30) was changed while the ratio of other additives remained unchanged. The original mechanical properties of Comparative Example 5 dropped sharply. Compared with Examples 1 to 5, the tensile strength was reduced by 9 to 11 MPa, and the elastic modulus was reduced by 327 to 419 MPa. In comparison, the high-performance thermoplastic starch-based blended plastics prepared in Examples 1 to 5 have significantly improved original mechanical properties and various physical properties compared to the comparative examples. Compared with the comparative examples, the tensile strength is increased to 8 to 15 MPa, and the elastic modulus is increased by 280 to 470 MPa. Moreover, the tensile strength is basically stable after repeated recycling and mixing. Both the tensile strength and elastic modulus are higher than those of the comparative examples, and are maintained at a relatively high performance level. This shows that the present invention can indeed effectively improve the value of TPS / PBAT. In the case of molecular chain breakage during the reprocessing process, the strength and modulus of the material can also be maintained at a relatively high level, which is very suitable for industrial mass-production and efficient processing. It is of great significance to reduce the preparation and recycling costs of TPS / PBAT plastics and expand their scope of application.

[0107] The above embodiments are merely examples of the technical solutions of the present invention. The imine bond dynamic crosslinking modification method of the high-performance thermoplastic starch-based blended plastic involved in the present invention is not limited to the contents described in the above embodiments, but is subject to the scope defined in the claims. Any modification, supplement or equivalent replacement made by a technician in the field of the present invention based on the embodiment is within the scope of protection required by the claims of the present invention.

Claims

1. A method for preparing a high-performance thermoplastic starch-based blended plastic TPS / PBAT, characterized in that: The steps include: Step (1), mixing starch and starch plasticizer and letting the mixture stand to obtain pre-plasticized starch; Step (2), melt-blending the obtained pre-plasticized starch with poly (butylene terephthalate-adipate) PBAT, 3-amino methyl crotonate AAME, and an initiator, cooling, and drying to obtain a grafted material; Step (3), melt blending the obtained grafted material with terephthalaldehyde TPA, cooling, and drying to obtain a high-performance thermoplastic starch-based blended plastic TPS / PBAT.

2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of starch to starch plasticizer is 70-80:20-40.

3. The preparation method according to claim 1, characterized in that: The starch plasticizer is selected from any one or more of water, glycerol, propylene glycol, and sorbitol.

4. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of pre-plasticized starch to PBAT is 80-90:10-20.

5. The preparation method according to claim 1, characterized in that: The mass of AAME in step (2) is 4%-6% of the total mass of pre-plasticized starch and PBAT.

6. The preparation method according to claim 1, characterized in that: The mass of the initiator in step (2) is 0.1%-0.25% of the total mass of the pre-plasticized starch and PBAT.

7. The preparation method according to claim 1, characterized in that: The amount of TPA added in step (3) is 0.35%-0.5% of the total mass of the pre-plasticized starch and PBAT.

8. The preparation method according to claim 1, characterized in that: The initiator is dicumyl peroxide DCP.

9. The preparation method according to claim 1, characterized in that: The temperature of melt blending in step (2) and step (3) is 145-160°C.

10. A high-performance thermoplastic starch-based TPS / PBAT blended plastic, characterized in that: The method is used to prepare the product according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of graphene / polyurea self-repairing and recoverable heat-conducting composite material with synergistic effect of hydrogen bonds and dynamic imine bonds

    CN117820602A

Cited By

  • Degradable waste liquid collecting bag and production method thereof

    CN120962978A

  • Viscous-dominated thermoplastic starch as well as preparation method and application thereof

    CN122037321A